If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + -4 = 4 Reorder the terms: -4 + 2a = 4 Solving -4 + 2a = 4 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2a = 4 + 4 Combine like terms: -4 + 4 = 0 0 + 2a = 4 + 4 2a = 4 + 4 Combine like terms: 4 + 4 = 8 2a = 8 Divide each side by '2'. a = 4 Simplifying a = 4
| 6p+5=-4-(1-4p) | | 17d+3d=20 | | -3n-7+5n=-6+2n-1 | | 0=12x^2-60x+50 | | 7x-3(4w+8)=11 | | x-21+2x=-5-2x-9 | | 47=6n-5+n | | 2p^2q^2+8pq-24=0 | | -24+3x=18-4x | | 16m-10m=6 | | t-5-4= | | -8-3(8)=4 | | 2.4(2)+1.2(2)-6.5=0.7 | | -39+x=33-5x | | 2a-5=-7 | | 75+6y=0 | | 3c^3-6c^2+3c=0 | | .5y+2=.25y+5 | | 5.3x^2-13x+14=0 | | 12x-11=4x-8 | | 9(3.75)-14+3(3.75-8)=7 | | 6(12.5)=x | | 1/2(x-3)+3/2-x=5x | | -15+9x=10x+9 | | 5u-4u=14 | | -5(3x-9)=10 | | 2z-z=2 | | 2x+4(-8)=0 | | 5a^2+26a+5=0 | | 14q-13q=7 | | 2u-u=13 | | (8-5x)-(5+7x)=0 |